2020
DOI: 10.1101/2020.04.14.041459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glycosaminoglycan binding motif at S1/S2 proteolytic cleavage site on spike glycoprotein may facilitate novel coronavirus (SARS-CoV-2) host cell entry

Abstract: Severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) has resulted in a pandemic and continues to spread around the globe at an unprecedented rate. To date, no effective therapeutic is available to fight its associated disease, COVID-19. Our discovery of a novel insertion of glycosaminoglycan (GAG)-binding motif at S1/S2 proteolytic cleavage site (681-686 (PRRARS)) and two other GAG-binding-like motifs within SARS-CoV-2 spike glycoprotein (SGP) led us to hypothesize that host cell surface GAGs m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 36 publications
(49 reference statements)
7
59
2
Order By: Relevance
“…spike. 8 Our data support a model in which the HS binding site of the RBD confers sequence specificity whereas that in S1/S2 proteolytic cleavage site enhances the affinity.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…spike. 8 Our data support a model in which the HS binding site of the RBD confers sequence specificity whereas that in S1/S2 proteolytic cleavage site enhances the affinity.…”
Section: Resultssupporting
confidence: 82%
“…7 A combined SPR and computational study showed that glycosaminoglycans can bind to the proteolytic cleavage site of the S1 and S2 protein. 8 HS are highly complex O-and N-sulfated polysaccharides that reside as major components on the cell surface and extracellular matrix of all eukaryotic cells. 9 Various proteins interact with HS thereby regulating many biological and disease processes, including cell adhesion, proliferation, differentiation and inflammation.…”
Section: Sars-mentioning
confidence: 99%
“…According to current reports, this heparin-binding motif may facilitate SARS-CoV-2 host cell entry 36 .…”
Section: Discussionmentioning
confidence: 92%
“…However, scienti c evidence shows that endocytosis of SARS-CoV also occurs through a novel, clathrinand caveolae-independent endocytic pathway, mediated by attachment to cell surface heparan sulfate proteoglycans (HSPGs) [29][30][31][32] . Meanwhile, it has been also revealed that the S1 subunit of the SARS-CoV-2 spike protein, the subunit responsible for cellular attachment, contains the heparin-binding core motif PRRAR [33][34][35][36] ( Supplementary Fig. S1).…”
Section: Development Of E Cient Therapeutics Against Covid-19 Is Hampmentioning
confidence: 99%
“…Studies of coronavirus-receptor interactions have implicated the sulfated glycosaminoglycans heparin and heparan sulfate in viral attachment to mammalian cells [1,2]. Recent work on the structure of the spike protein of SARS-CoV-2 has provided detail about the glycosylations of the spike protein and interactions between the spike protein and carbohydrates [3,4]. Findings suggest potential for both proteincarbohydrate and carbohydrate-carbohydrate interactions between the spike glycoprotein and cell receptors.…”
Section: Introductionmentioning
confidence: 99%